O trabalho humano sob a ótica acadêmica: um olhar sobre a categoria trabalho na formação em psicologia - Luciana Rodrigues Martins (2006)
It is a research, of qualitative character, privileging the knowledge production in the life of the intersubjectivity, under the theoretical contribution of Psychosociology (French line), it has as theme The Emergency of Category Work in the Academic Formation in Psychology. Itseeks, in general sense, to understand as the process of production of knowledge is engendered on the human work in the academic space of the psychology, tends in view that, historically, the work has been relegated to inferior plans in the formation in psychology. However, leaving of the statute of centrality of this category in the subjects constitution, being observed the phenomena produced in the relationship capital-work - that rebounds about the psychic health -, it stands out the need to assure the knowledge concerning that category, given your fundamental aspect in the praxis in psychology. The general panorama of the formation, represented by the five institutions researched in the metropolitan area of Belo Horizonte, it appears for positive processes of transformations, in that the category has been contemplated in the widest form, especially through the academic activities, that articulate work and clinic. Tends in view imperatives of social dynamics, the field of the work is shown more consolidated in the academic universe, in consequence of the scientific productions in this area, resultants of the qualification of the faculty